Investigation of the Feasibility and Safety of a Highly Intensive Penetration Technique for Recanalization in Severe Calcified Femoropopliteal Occlusive Lesions: A Retrospective Observational Study - Shinsuke Mori; Keisuke Hirano; Yusuke Setonaga; Toshihiko Kishida; Tomoya Fukagawa; Kohei Yamaguchi; Masafumi Mizusawa; Masakazu Tsutsumi; Norihiro Kobayashi; Yoshiaki Ito (Health Science Reports)
ABSTRACT Background and Aims When dealing with severely calcified lesions in endovascular therapy (EVT) for lower extremity artery disease (LEAD), navigating through severely calcified chronic total occlusion (CTO) using hard‐tip guidewires can be challenging. To address this issue, we employed a novel highly intensive penetration (HIP) technique. This technique involves modifying the tail of a 0.035‐inch guidewire to enhance its penetration capability, thus enabling effective navigation through the calcified lesion and facilitating the EVT procedure. This study aimed to assess the feasibility and safety of the HIP technique. Methods This single‐center, retrospective study enrolled 27 consecutive patients (29 limbs) who underwent the HIP technique for the recanalization of calcified femoropopliteal CTO lesions that were resistant to penetration by high‐tip load (≧ 40 g) guidewires between January 2015 and April 2023. Statistical analyses were performed using JMP 13 software. Results The mean patient age was 75.9 ± 10.1 years. The proportion of men, patients with hypertension, patients with diabetes mellitus, and patients on hemodialysis was 78%, 59%, 41%, and 44%, respectively. The crossover approach was selected for 55% of the patients. The reference vessel diameter was 5.3 ± 0.6 mm, and the lesion length was 19.7 ± 12.0 cm. The target lesions were predominantly located in the superficial femoral artery (76%). In‐stent occlusion was treated in 14% of patients. The HIP technique was successfully performed in 79% of patients, and the complication rate of vascular perforation was 7%. Conclusion The HIP technique demonstrates remarkable effectiveness in navigating through highly calcified lesions, offering a reliable method for successful recanalization in challenging cases.